Physical characteristic and germination of hibiscus sabdariffa l. following hydration treatments - Syazwanie, binti Dzulhaimi (Universiti Malaysia Sarawak (UNIMAS), 2012)
A study was conducted to determine the physical characteristics and to assess and evaluate the effectiveness of hydration techniques in improving the performance of HibisclIs sabdariffa L. seeds. The average length, width and thickness obtained for H. sabdariffa seeds were 5.39 mm, 4.55 mm and 2.34 mm, respectively. The average weight for a single seed was 0.02 g and it was estimated that one kg weight contained approximately 50,000 seeds. This indicated that the seeds used in this experiment were small. In hydration treatment, seeds of H. sabdariffa were soaked in water at temperature 28, 30, 35 and 40°C for 0,2,4,6, 8, 10 and 12 hours and were evaluated for moisture content and germination. Results indicated that hydration treatment was not suitable for H. sabdariffa seeds as it did not improved the germination. The highest germination percentage of H. sabdarifJa seeds following hydration treatment was 29% which was obtained for 2 hours hydration at 30°C.